2013
DOI: 10.1603/me12083
|View full text |Cite
|
Sign up to set email alerts
|

Does Autocthonous Primary Production Influence Oviposition byAedes japonicus japonicus(Diptera: Culicidae) in Container Habitats?

Abstract: Aedes (Finlaya) japonicus japonicus (Theobald) (Diptera: Culicidae) is recently invasive in North America and has expanded its range rapidly since 1998. Throughout its native and expanded range, Ae. j. japonicus larvae are commonly observed in many types of natural and artificial water-filled containers that vary in organic matter content and exposure to sunlight. Larvae are most often found in containers with decaying leaf material or algae, and we postulated that the added autocthonous primary production fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In some areas in North America they preferentially select rock pools (Juliano & Lounibos, 2005) particularly in areas with low summer temperatures (Andreadis & Wolfe, 2010) or high degrees of shade (Armistead et al ., 2012). Elsewhere in the USA and Japan, larvae have been found in various aquatic habitats with varying sunlight, elevation and detrital content, and within both urban and rural settings (Lorenz et al ., 2013). Its distribution and aquatic habitats in North America overlap with Ae.…”
Section: Brief History Of Spread and European Distributionmentioning
confidence: 99%
“…In some areas in North America they preferentially select rock pools (Juliano & Lounibos, 2005) particularly in areas with low summer temperatures (Andreadis & Wolfe, 2010) or high degrees of shade (Armistead et al ., 2012). Elsewhere in the USA and Japan, larvae have been found in various aquatic habitats with varying sunlight, elevation and detrital content, and within both urban and rural settings (Lorenz et al ., 2013). Its distribution and aquatic habitats in North America overlap with Ae.…”
Section: Brief History Of Spread and European Distributionmentioning
confidence: 99%
“…j. japonicus readily oviposits in open areas (61), but it is not clear whether larval success is related to habitat microsite characters. Lorenz et al (61) hypothesized that algae in sunlit habitats could play a role in the invasion success, but they found no overall preference for oviposition in containers that had been exposed to sun (high algal production) versus those that were shaded (low algal production). Sota et al (98) suggested that Ae.…”
Section: Larval Habitats In North America and Europementioning
confidence: 99%
“…Generally, there appears to be weak or absent effects of algae on growth rate or population sizes of container species (Kling et al 2007, Lorenz et al 2013) and Ae. albopictus specifically (Yee et al 2015a).…”
Section: Larval Microorganism Food Sourcesmentioning
confidence: 99%